Factor Affecting the Exchange rate of Lao kip against the US Dollar - DALAPHONE , Valasine; CHANTHAVONE , Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Currency Exchange Rate is one of a significant factor to consecutively in international transactions such as foreigner trading, investment including international supporting must use currency exchange rate to communicate with products and services. Since 1986, Lao PDR has opened the country by transitioning from Planed economy to a market economy on September 13th 1995, an official exchange rate has canceled and change into floating exchange rate but to determine exchange rate nowadays is related to the commercial partners such Thai (baht) and United State of America (dollar) that because of the economic is not solid but depend on foreign products and services, the amount of an export to foreign has decrease causes of world financial and economic crisis makes the value of kip is depreciated. To study on factor of exchange rate affected from kip to dollars has against in conducting the monetary policy, which is a quantitative and qualitative analysis of quarterly data from 2004-2019 by testing the factors affecting in short-term and long-term exchange rates in 2020. The study case found that the Export value, Current account, Inflation rate, bank interest rate, Loan interest rate (Type of customers: A) and consumer price index affected to exchange rate make adjustments to balancing in a long-term but the Export Value and inflation rate has relate in opposite with because of the country imported products from foreign countries over than exports and a trading with United State of America and Europe is less than ever, so it makes the inflation adjustments are contrary to the exchange rate. The short-term adjustment of Export value, bank interest rate, Loan interest rate and consumer price index causes to dollar exchange rate has changed to 38,51% in balancing adjustments. When the forecasting of testing exchange rate in 2020 by ARIMA (0.1.1) show the dollars has decrease than a last quarterly.